2008
DOI: 10.1007/s11427-008-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of aucubin in primary diabetic encephalopathy

Abstract: Hippocampal neuronal apoptosis accompanied by impairment of cognitive function occurs in primary diabetic encephalopathy. In this study, we investigated the neuroprotective mechanism of the iridoid glycoside, aucubin, using rats (n=8). Diabetes mellitus was induced in the rats by intraperitoneal (i.p.) injection of streptozotocin (60 mg/kg body weight). After 65 d, half of the DM rats were administered aucubin (5 mg/kg; i.p.) for 15 d, yielding treatment DM+A. A third group of rats received no streptozotocin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Aucubin, a natural compound has been found in various plants including leaves of Aucuba japonica [15] and Eucommia ulmoides [16], proves to possess a variety of pharmacological effects [17][18][19]; [20], notably, anti-inflammatory effect [21]. It has been reported to have blocked the translocation of NF-κB by inhibition of IκB degradation and phosphorylation, a critical step in early inflammatory responses [22].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Aucubin, a natural compound has been found in various plants including leaves of Aucuba japonica [15] and Eucommia ulmoides [16], proves to possess a variety of pharmacological effects [17][18][19]; [20], notably, anti-inflammatory effect [21]. It has been reported to have blocked the translocation of NF-κB by inhibition of IκB degradation and phosphorylation, a critical step in early inflammatory responses [22].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Com estrutura molecular semelhante ao catalpol e de forma similar com eficaz ação antiapoptótica, a acubina possui função neuroprotetora associada ao favorecimento da atividade de enzimas antioxidantes endógenas e a capacidade de eliminar o excesso de ER e proteger contra o dano a lipídeos de membrana, melhorando a glicemia em modelo experimental de encefalopatia diabética 84 . Dados de estudos experimentais anteriores demonstram que a acubina pode evitar a apoptose modulando a expressão de genes relacionados a apoptose Bcl-2 e Bax 85 . O efeito neuroprotetor, a melhora da cognição e proteção contra a perda de neurônios ocorre tanto em curto quanto em longo prazo no tratamento experimental com acubina 86 .…”
Section: Antioxidantes E Encefalopatia Diabéticaunclassified
“…Recently, its anti-inflammatory and antioxidative functions have become a focus of research. Studies have shown that Au provides neuroprotective effects via anti-inflammation and anti-oxidative properties [26][27][28][29][30]. Nevertheless, its molecular mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 99%